PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, SOLVABILITAS, DAN OPINI AUDIT TERHADAP AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2020 - Dinata , I Gede Arya Mahendra; Jayanti, Luh Gede Pande Sri Eka; Sutapa , I Nyoman (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2025)
This study aims to determine the effect of Company Size, Profitability, Solvency, and Audit Opinion on Audit Delay in Manufacturing Companies listed on the Indonesia Stock Exchange for the 2018-2020 Period. The population in this study was all manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020 and the sample in this study was 77 manufacturing companies that had met the criteria using purposive sampling. The type of data in the study is quantitative data. This study used secondary data taken through the official website of the Indonesia Stock Exchange. The data analysis technique used is multiple linear regression analysis where the independent variables are company size, profitability, solvency and audit opinion while the dependent variables are audit delay. The results showed that the size of the company negatively affects the audit delay, profitability does not Effect on audit delay, solvency does not affect audit delay and audit opinion has a negative and significant effect on audit delay.